The Relevance of Maqashid Sharia in Green Economy (Study of Coastal Tourism Area Mangrove Park Labuhan, Bangkalan-Madura) - Nasrulloh Nasrulloh; Fiki Andrean Yahya (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
Bangkalan Regency has various kinds of tourism potential, especially coastal tourism. One of the coastal tourism that has the potential to be developed is the Labuhan Mangrove Tourism. These attractions have several potentials including strategic locations, exotic views, and as a means of public education. This causes the need for a system or concept of coastal tourism management that is appropriate and can be implemented. The purpose of this research is to implement the green economy concept as an alternative solution for coastal tourism management and to maintain the conservation of the surrounding natural environment so that it runs in harmony and sustainability in order to maintain the sustainability of the local community's economic system. This research used descriptive qualitative method. Data were collected through observation, documentation, and interviews with local governments, tourism managers, visitors and the surrounding community. This data is then recorded and strengthened through literature study. The results showed that the implementation of sustainable development of coastal tourism at the Labuhan Mangrove tourism object through the application of green economy concepts including planting mangrove seedlings, conserving coral reefs, providing landfills for final disposal in the tourist environment of Labuhan. The construction of embankments around the coast is also important to minimize coastal abrasion. Environmental protection is also included in the protection of religion, because Islam forbids all actions that destroy everything on earth. Protecting the earth by not using it will ensure human survival and at the same time carry out religious orders